An Empirical Analysis of the Growth-Health Relationship in Pakistan - Khalid, Nayab; Qayyum, Aaqib (Yayasan Ahmar Cendekia Indonesia, 2021)
The purpose of this study is to examine Pakistan's health sector issues and the critical ties between health indicators and economic growth. ARDL analysis has been applied on the data set of Pakistan’s economy, in the time reference to 1990-2020. The study revealed that the important ties between GDP, foreign direct investment, fertility and life expectation in the short run are strong, while mortality rate is negative, but have a significant impact on economic development. The fertility rate has a huge effect on GDP in long-term, while affecting foreign direct investment. The study achieves that countries with developing economic growth will focus more on improving human capital well-being.